Chinese stroke association guidelines on reperfusion therapy for acute ischaemic stroke 2024 - Liping Liu; Anding Xu; Xin Wang; Yongjun Wang; Yilong Wang; Zhongrong Miao; Yuming Xu; Benyan Luo; Bin Peng; Yong Huo; Qiang Dong; Zixiao Li; et al. (Stroke and Vascular Neurology)
Background Stroke remains a major global health challenge, with China experiencing a significant burden due to its high incidence and severe outcomes. Reperfusion therapies, such as intravenous thrombolysis and endovascular thrombectomy, have shown substantial benefits in improving early outcomes for ischaemic stroke. Recent clinical trials have validated the safety and efficacy of a broader range of thrombolytic agents and expanded the eligible patient populations for both intravenous thrombolysis and mechanical thrombectomy. This guideline aims to provide the latest evidence-based insights in the field of reperfusion therapy.Methods The Chinese Stroke Association (CSA) established a writing group to develop updated guidelines on reperfusion therapy for acute ischaemic stroke. A comprehensive search of MEDLINE (via PubMed) was conducted up to 30 September 2024. Experts in the field of stroke engaged in extensive discussions, both online and offline, to evaluate the latest evidence. Each recommendation was graded using the CSA’s class of recommendation and level of evidence in the Guideline Development Manual of the CSA.Results This guideline, reviewed and approved by the CSA Guidelines Writing Group, outlines the criteria for patient selection for thrombolysis and thrombectomy and summarises the latest evidence on various thrombolytic drug options to support decision-making in reperfusion therapy. Additionally, the guideline includes green channel flow charts for intravenous thrombolysis and mechanical thrombectomy, designed to assist clinicians in optimising their clinical decisions.Conclusion This guideline updates the latest advancements in the field of reperfusion therapy for acute ischaemic stroke. It is anticipated that future clinical research will further advance areas such as innovative thrombolytic agents, expanded indications for thrombolysis and mechanical thrombectomy.